An integrated modeling approach for assessing management objectives for mule deer in central British Columbia - Ian W. Hatter; Patrick Dielman; Gerald W. Kuzyk (Wildlife Society Bulletin)
ABSTRACT We used an integrated Bayesian state‐space population model to assess whether management objectives were met before (1995–2003), during (2004–2010), and after (2011–2013) antlerless permits to harvest mule deer (Odocoileus hemionus) were increased in response to stakeholder concerns in central British Columbia, Canada. Data inputs included 19 years of harvest data, 7 years of autumn age–sex composition data, 17 years of spring age–sex composition data, and 15 years of a population index. Management objectives were to maintain a spring population of 7,000–9,000 deer and a posthunt adult sex ratio of 20–30 males:100 females. An 8.5‐fold increase in antlerless permits raised the antlerless harvest rates from 1.0% (1995–2003) to 4.8% (2004–2010). Antlerless harvest rates decreased to 2.8% following a 53% decrease in permits from 2011 to 2013. Population projections from 2014 to 2018 fell within the bounds of the management objectives, but 95% credibility intervals revealed great uncertainty in population size and composition. We recommend a structured, adaptive approach to mule deer management that includes annual adjustment of harvests, monitoring, and modeling, with an open‐ended stakeholder engagement process to ensure objectives remain relevant, measurable, and achievable. © 2017 The Wildlife Society.